Sarcoidosis development during ulcerative colitis remission in a patient with a susceptible human leukocyte antigen genotype - Sumi, Toshiyuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
The combination of sarcoidosis and ulcerative colitis (UC) is very rare, and its pathogenesis remains unknown. Hereditary factors as well as environmental factors have been speculated, including an association between human leucocyte antigen (HLA) genotype. A 62-year-old Japanese woman with UC presented complaining of a cough. Abnormal shadows were evident on chest X-ray during mesalazine therapy. Multiple indolent subcutaneous nodules were also detected. Transbronchial lung and skin biopsies showed non-caseous epithelioid granulomas, which was pathologically compatible with sarcoidosis. After steroid therapy, she became asymptomatic and the abnormal shadows and the subcutaneous nodules disappeared. HLA analysis revealed that she harbored the sarcoidosis-related HLA DR14 allele, as well as UC-related HLA B52 and DR15 alleles. The present case suggested that a susceptible HLA genotype may influence the onset of the combination of sarcoidosis and UC.